Organizational climate and its role in promoting organizational citizenship behaviors A case study of the University of Babylon Presidency - Jaber, Batool Fadel (Majallat Jāmiʻat Bābil, 2025)
The organizational climate is expressed through Android, which has diversified the internal work environment, which is directed by the workers to cooperate with the internal work environment of the organization, which is a result of the work policies and systems that were organized for the direction and philosophy of the top management. In it. The importance of the research lies in identifying the nature of the organizational climate in any institution that helps and contributes to providing a suitable work environment, and the aim of the research is to identify the role of the organizational climate in its following dimensions:)Organizational structure/communication style/leadership style/decision making/nature of work) As an independent variable and organizational citizenship with its dimensions (altruism/politeness/balance and compliance/sportsmanship/civilized behavior) As a dependent variable, the University of Babylon was chosen as a field community for the research. The size of the community was (202) teachers to apply the research frameworks, and the sample size was (133) teachers. The questionnaire was distributed to them. The research hypotheses were tested and analyzed using the ready-made software package (SPSS V.27). I have reached the conclusion that the study sample tends to engage in voluntary behaviors that fall within what is known as organizational citizenship behavior at a high level. Through this study, it became clear that organizational citizenship behavior has an effective role in achieving organizational effectiveness through the positive effects it leaves behind. This calls for strengthening such behaviors in institutions in general and the university institution in particular for the growth, development and success of the educational process.